SURGICAL ANALYSIS OF LYMPH NODE POSITIVITY AFTER NEOADJUVANT THERAPY - Bernardi, Rodrigo Ferreira; Hatschbach, Sergio Bruno Bonatto; Linhares, José Clemente; Hubie, Danila Pinheiro; Silva, Rafaela da (Mastology, 2019)
Introduction: Breast cancer is the most prevalent tumor in women around the world, affecting 1 in 10 women in Brazil. Therefore, providing surgeries that can increase cure rates and provide less comorbidities than those that occur today is a challenge. Until the last decade, performing lymphadenectomy, after neoadjuvant therapy was mandatory. However, new studies could prove that, for some cases, the sentinel lymph node biopsy can be an option. Objective: To analyze the positivity rates of lymphadenectomy, after neoadjuvant therapy. Methods: A total of 152 patients who underwent lymphadenectomy were assessed, from 2012 to 2014; they were separated into two groups of arms: those that had clinically positive armpit results before chemotherapy in one arm, and those that had negative armpit results before chemotherapy. Results: Out of 152 patients, 57 had negative armpit results before chemotherapy, 71% continued to have negative results following lymphadenectomy. In the group containing 95 patients with positive armpit results (following neoadjuvant therapy), 43.6% of them were free from neoplasms after undergoing lymphadenectomy. Discussion: T he r esults o f t his s tudy w ere similar to those found in worldwide literature for lymph node rates in all groups. It means that both the staging before chemotherapy and neoadjuvant therapy are performed with the same efficacy rates as in other studied hospitals. Moreover, there is evidence on the authorization to perform sentinel lymph node biopsy after chemotherapy in those patients who had clinically negative armpit results prior to neoadjuvant therapy. Conclusion: Sentinel lymph node biopsy is a safe and efficient technique to be used in patients who underwent chemotherapy and had negative armpit results. Whenever needed, such technique should always be encouraged.